Candidate genetic analysis of plasma high-density lipoprotein-cholesterol and severity of coronary atherosclerosis - Gotto Antonio M; Willerson James T; Lombardi Raffaella; Todd Josh; Cilingiroglu Mehmet; Chen Suet; Ballantyne Christie M; Marian AJ (BMC, 2009)
Abstract Background Plasma level of high-density lipoprotein-cholesterol (HDL-C), a heritable trait, is an important determinant of susceptibility to atherosclerosis. Non-synonymous and regulatory single nucleotide polymorphisms (SNPs) in genes implicated in HDL-C synthesis and metabolism are likely to influence plasma HDL-C, apolipoprotein A-I (apo A-I) levels and severity of coronary atherosclerosis. Methods We genotyped 784 unrelated Caucasian individuals from two sets of populations (Lipoprotein and Coronary Atherosclerosis Study- LCAS, N = 333 and TexGen, N = 451) for 94 SNPs in 42 candidate genes by 5' nuclease assays. We tested the distribution of the phenotypes by the Shapiro-Wilk normality test. We used Box-Cox regression to analyze associations of the non-normally distributed phenotypes (plasma HDL-C and apo A-I levels) with the genotypes. We included sex, age, body mass index (BMI), diabetes mellitus (DM), and cigarette smoking as covariates. We calculated the q values as indicators of the false positive discovery rate (FDR). Results Plasma HDL-C levels were associated with sex (higher in females), BMI (inversely), smoking (lower in smokers), DM (lower in those with DM) and SNPs in APOA5, APOC2, CETP, LPL and LIPC (each q ≤0.01). Likewise, plasma apo A-I levels, available in the LCAS subset, were associated with SNPs in CETP, APOA5, and APOC2 as well as with BMI, sex and age (all q values ≤0.03). The APOA5 variant S19W was also associated with minimal lumen diameter (MLD) of coronary atherosclerotic lesions, a quantitative index of severity of coronary atherosclerosis (q = 0.018); mean number of coronary artery occlusions (p = 0.034) at the baseline and progression of coronary atherosclerosis, as indicated by the loss of MLD. Conclusion Putatively functional variants of APOA2, APOA5, APOC2, CETP, LPL, LIPC and SOAT2 are independent genetic determinants of plasma HDL-C levels. The non-synonymous S19W SNP in APOA5 is also an independent determinant of plasma apo A-I level, severity of coronary atherosclerosis and its progression.